Endocrine abnormality in paraneoplastic syndrome. Issue 3 (May 2022) - Onyema, Michael C.; Drakou, Eftychia E.; Dimitriadis, Georgios K.
Abstract : Paraneoplastic syndromes denote rare but notable phenomena caused by the tumour mediated release of bioactive substances. Peptide and non-peptide hormone causes are explored with a particular focus on pathogenesis, symptoms, diagnosis and treatment. Early detection and management of paraneoplastic syndromes can improve morbidly and mortality; definitive treatment remains effective surgical or anti-tumour therapies. Pituitary autoimmunity may provide a novel presentation of paraneoplastic syndromes for which further research is warranted.